The effectiveness of Problem Based Learning (PBL) model with cooperative type Think Pair Share (TPS) in terms of self regulated learning and student achievement result - A Fitriani (Pascasarjana Universitas Pendidikan Indonesia, 2018)
This research aims to describe the problem-based learning model with the cooperative type of think pair share in terms of self-regulated learning and student learning preservation. This research is a quasi-experimental research with quantitative approach. Instruments used to collect data include student achievement test and self regulated learning questionnaire. The results of research at the level of significance 5% indicates that the model of learning-based learning problems with cooperative set type think pair share effective review of self-regulated learning and student achievement. This is indicated by the t test value of self regulated learning of 3.95 and the value of t test for student achievement of 9.29, which is greater than t table of 1.64.